The sound of ruins: Sigur Ros' Heima and the post-rock elegy for place - Fletcher, Lawson (Trinity College Dublin, 2012)
Amongst the ways in which it maps out the geographical imagination of place, music plays a unique role in the formation and reformation of spatial memories, connecting to and reviving alternative times and places latent within a particular environment. Post-rock epitomises this: understood as a kind of negative space, the genre acts as an elegy for and symbolic reconstruction of the spatial erasures of late capitalism. After outlining how post-rock’s accommodation of urban atmosphere into its sonic textures enables an ‘auditory drift’ that orients listeners to the city’s fragments, the article’s first case study considers how formative Canadian post-rock acts develop this concrete practice into the musical staging of urban ruin. Turning to Sigur Ros, the article challenges the assumption that this Icelandic quartet’s music simply evokes the untouched natural beauty of their homeland, through a critical reading of the 2007 tour documentary Heima. A closer reading of the band’s audiovisual practice reveals a counter-geography of Iceland, in which the country’s decaying industrial past is excavated and its more recent ecological failures are accounted for. As with post-rock more generally, this proposes a more complex relationship between music, place and memory than that offered by notions of reflection and nostalgia, which instead emerges as a melancholic mourning for spatial pasts.